Imperfect Legal Unbundling of Monopolistic Bottlenecks - Felix Höffler; Sebastian Kranz (University of Bonn, Bonn Graduate School of Economics (BGSE), 2007)
We study an industry with a monopolistic bottleneck (e.g. a transmission network) supplying an essential input to several downstream firms. Under legal unbundling the bottleneck must be operated by a legally independent upstream firm, which may be partly or fully owned by an incumbent active in downstream markets. Access prices are regulated but the upstream firm can perform non-tariff discrimination. Under perfect legal unbundling the upstream firm maximizes only own profits; with imperfections it considers to some extend also the profits of its downstream mother. We find that reducing imperfections in legal unbundling (keeping ownership fixed) generally increases total output. Increasing the incumbent's ownership share increases total output if imperfections are sufficiently small, otherwise the effects are ambiguous. Surprisingly, higher ownership shares of the downstream incumbent may sometimes lead to lower degrees of imperfections. Our analysis suggests that consumers may benefit most from legal unbundling with strong regulation and parts of ownership given to a minority outside shareholder.
Keywords: L11; L42; L43; L51; 330; Network industries; regulation; vertical relations; ownership; corruption; sabotage; Vertikale Konzentration; Lieferanten-Kunden-Beziehung; Netzzugang; Unternehmensentflechtung; Monopol; Investition; Eigentum; Theorie